Endoscopic closure using a dedicated device following gastric endoscopic submucosal dissection: Multicenter, prospective, observational pilot study - Shiotsuki, Kazuo; Takizawa, Kohei; Nose, Yohei; Kondo, Yuki; Homma, Hitoshi; Inada, Taisuke; Daikaku, Mao; Maehara, Kosuke; Fukuda, Shin-ichiro; Aoki, Hironori; Sumida, Yorinobu; Akiho, Hirotada; Watari, Jiro; Nakajima, Kiyokazu (Endoscopy International Open, 2025)
Development of a simple, optimized closure method for mucosal defects left by gastric endoscopic submucosal dissection (ESD) is warranted. Herein, we developed a novel and dedicated closure device called FLEXLOOP and aimed to assess feasibility and safety of the closure using FLEXLOOP following gastric ESD.This multicenter, prospective, observational study enrolled patients clinically diagnosed with gastric neoplasms < 30 mm in size. Following gastric ESD, closure of the mucosal defect was performed using a FLEXLOOP with standard clips. The primary outcome was the complete closure rate. The secondary outcomes were procedure time, number of clips, sustained closure rate on second-look endoscopy on postoperative days (PODs) 5 to 7, and rate of post-ESD bleeding.Overall, 35 patients were included in this study. The median specimen size was 32 mm. The mucosal defect was completely closed in 31 patients (89%; 95% confidence interval, 73%-99%) and incompletely closed in four patients (11%). Median closure time was 11 minutes and median number of clips was 10. Second-look endoscopy performed on PODs 5 to 7 demonstrated sustained, partially sustained, and unsustained closures in seven (20%), 22 (63%), and six patients (17%), respectively. Post-ESD bleeding and complications related to FLEXLOOP were not observed.Closure using FLEXLOOP is feasible and safe. Our technique using this new device can be an attractive option for more easily closing mucosal defects. However, further clinical research is warranted to confirm that this technique can prevent delayed complications.
Keywords: Endoscopy Upper GI Tract; Endoscopic resection (ESD, EMRc, ...); Barrett's and adenocarcinoma; Precancerous conditions & cancerous lesions (displasia and cancer) stomach